A COMPARATIVE STUDY OF THE 5 ENGLISH VOWELS AND THE 6 STABLE UZBEK VOWELS (Ustozlar uchun, 2026)
This article presents a comparative analysis of the vowel systems of the English and Uzbek languages, focusing on the 5 basic English vowel phonemes and the 6 stable Uzbek vowels. It examines the phonetic and phonological differences between the two systems, including vowel quality, quantity, and position. The study highlights how the mismatches between these systems can lead to phonetic interference in the pronunciation of Uzbek learners of English.